Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 102854 by Sontsaronald last updated on 11/Jul/20

Answered by Ar Brandon last updated on 11/Jul/20

arctan(ch(x))=arctan((1/(sh(x))))  ⇒ ch(x)=(1/(sh(x))) ⇒ 2sh(x)ch(x)=2 ⇒ sh(2x)=2  ⇒ (1/2)(e^(2x) −e^(−2x) )=2 ⇒ e^(4x) −4e^(2x) −1=0  ⇒ e^(2x) =((4±(√(20)))/2)=2±(√5)  ⇒2x=ln(2+(√5)) ⇒ x=((ln(2+(√5)))/2)    Voici ce que je pense. Je me demande s′il en  faut plus.

$$\mathrm{arctan}\left(\mathrm{ch}\left(\mathrm{x}\right)\right)=\mathrm{arctan}\left(\frac{\mathrm{1}}{\mathrm{sh}\left(\mathrm{x}\right)}\right) \\ $$$$\Rightarrow\:\mathrm{ch}\left(\mathrm{x}\right)=\frac{\mathrm{1}}{\mathrm{sh}\left(\mathrm{x}\right)}\:\Rightarrow\:\mathrm{2sh}\left(\mathrm{x}\right)\mathrm{ch}\left(\mathrm{x}\right)=\mathrm{2}\:\Rightarrow\:\mathrm{sh}\left(\mathrm{2x}\right)=\mathrm{2} \\ $$$$\Rightarrow\:\frac{\mathrm{1}}{\mathrm{2}}\left(\mathrm{e}^{\mathrm{2x}} −\mathrm{e}^{−\mathrm{2x}} \right)=\mathrm{2}\:\Rightarrow\:\mathrm{e}^{\mathrm{4x}} −\mathrm{4e}^{\mathrm{2x}} −\mathrm{1}=\mathrm{0} \\ $$$$\Rightarrow\:\mathrm{e}^{\mathrm{2x}} =\frac{\mathrm{4}\pm\sqrt{\mathrm{20}}}{\mathrm{2}}=\mathrm{2}\pm\sqrt{\mathrm{5}} \\ $$$$\Rightarrow\mathrm{2x}=\mathrm{ln}\left(\mathrm{2}+\sqrt{\mathrm{5}}\right)\:\Rightarrow\:\mathrm{x}=\frac{\mathrm{ln}\left(\mathrm{2}+\sqrt{\mathrm{5}}\right)}{\mathrm{2}} \\ $$$$ \\ $$$${Voici}\:{ce}\:{que}\:{je}\:{pense}.\:{Je}\:{me}\:{demande}\:{s}'{il}\:{en} \\ $$$${faut}\:{plus}. \\ $$

Commented by Sontsaronald last updated on 11/Jul/20

ahahahaha vous etes un genie.merci beaucoup

$${ahahahaha}\:{vous}\:{etes}\:{un}\:{genie}.{merci}\:{beaucoup} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com